2013
DOI: 10.1177/0300060512474124
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of invasion of hepatocellular carcinoma cells through lysophosphatidic acid receptor

Abstract: Objectives: Lysophosphatidic acid (LPA) is a bioactive lipid mediator involved in tumour progression, cell invasion and metastasis. The mechanism of action of LPA in the invasive and metastatic capacity of human hepatocellular carcinoma (HCC) is not fully understood. This study investigated the effects of LPA on HCC cell invasion and induction of matrix metalloproteinase (MMP) À2 and À9. Methods: LPA receptor levels in HCC cell lines were detected by Western blot analysis; HCC cell invasion was analysed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Association of LPA-mediated signaling with tumor progression in carcinomas other than urothelial carcinoma has been reported. In hepatocellular carcinoma, LPA stimulates cancer cell invasion in a LPA-receptor dependent manner [19]. In prostate carcinoma, increased LPA-dependent RHO signaling enhances tumor invasion [20].…”
Section: Resultsmentioning
confidence: 99%
“…Association of LPA-mediated signaling with tumor progression in carcinomas other than urothelial carcinoma has been reported. In hepatocellular carcinoma, LPA stimulates cancer cell invasion in a LPA-receptor dependent manner [19]. In prostate carcinoma, increased LPA-dependent RHO signaling enhances tumor invasion [20].…”
Section: Resultsmentioning
confidence: 99%
“…Ki16425 was reportedly able to significantly reduce pancreatic cancer development [105] and reduce hepatocarcinoma tumor cell invasion and lung metastases [77]. Furthermore, Ki16452 can significantly reduce LPA-related HCC cell invasion [106]. Moreover, silencing of LPA1 or treatment with Ki1625 was demonstrated to lead to the inhibition of sphere-forming ability, tumorigenicity, and drug resistance in ovarian CSC [61].…”
Section: Development Of Inhibitors Against the Atx-lpa Signaling Axismentioning
confidence: 99%
“…Defining the mechanisms regulating HCC invasion may identify novel elements, which may be exploited therapeutically to reduce metastasis and improve patient survival. The process of metastasis involves several steps, including the detachment of cancer cells from the primary tumour, followed by the migration, adhesion and invasion of cancer cells into blood or lymphatic vessels; cancer cells then undergo extravasation and subsequently interact with target tissues, where they form metastastic foci in distant organs (41). The destruction of the extracellular matrix (ECM) by enzymes is an essential initial step in the processes of tumor cell invasion and metastasis, and several studies have reported that, among the enzymes responsible for ECM degradation, MMPs are have a critical role (42,43).…”
Section: Mmp-9 Is a Direct Target Gene Of Mir-133a In Hccmentioning
confidence: 99%